Chagas Disease: Still Many Unsolved Issues. (29th June 2014) - Álvarez, José M.; Fonseca, Raissa; Borges da Silva, Henrique; Marinho, Cláudio R. F.; Bortoluci, Karina R.; Sardinha, Luiz R.; Epiphanio, Sabrina; D'Império Lima, Maria Regina
Abstract : Over the past 20 years, the immune effector mechanisms involved in the control of Trypanosoma cruzi, as well as the receptors participating in parasite recognition by cells of the innate immune system, have been largely described. However, the main questions on the physiopathology of Chagas disease remain unanswered: "Why does the host immune system fail to provide sterile immunity?" and "Why do only a proportion of infected individuals develop chronic pathology?" In this review, we describe the mechanisms proposed to explain the inability of the immune system to eradicate the parasite and the elements that allow the development of chronic heart disease. Moreover, we discuss the possibility that the inability of infected cardiomyocytes to sense intracellular T. cruzi contributes to parasite persistence in the heart and the development of chronic pathology.